The pedagogical intervention of youth volleyball coaches - S. Santos; I. Mesquita; F. Pereira; M. P. Moreno (Asociación Española de Ciencias del Deporte, 2010)
The present study aims to characterize the pedagogical intervention of youth volleyball coaches, in relation to the practice type, the task's nature and the moment of intervention. 24 Portuguese coaches of youth teams participated in the study. Inferential statistics and Spearman's correlation coefficient were applied to analyse the association between the type of practice and the task's didactic nature. This study has showed that: the majority of youth coaches tend to intervene through feedback, to use over all refining tasks and acquisition tasks; when using a type of practice related to the acquisition of techniques, coaches employ more frequently introduction and extension tasks; in turn, when they appeal to a type of practice related to the game action's structuring, coaches use more often information and refining tasks. Finally, the opposition game as associated to application tasks. Key Words:coaching,  pedagogical intervention, volleyball,  practice structuring.